PENGARUH LIVING VALUES EDUCATION PROGRAM (LVEP) TERHADAP PENANAMAN KARAKTER NASIONALISME SISWA SD DALAM PEMBELAJARAN TEMATIK - An-Nisa Apriani; Indah Perdana Sari; Intan Kurniasari Suwandi (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
Living Values Education Program (LVEP) is one of the educational programs, which can facilitate the students to explore and develop the twelve universal values, which are cooperation, freedom, happiness, honesty, humility, love, peace, respect, responsibility, simplicity, tolerance, and unity. This research aims to know the influence of LVEP towards character building on the 3rd grade students in elementary school, within the topic of nationalism on the thematic learning. This type of research is quasi experiment design by utilizing pretest-posttest control group design. The population of this research is the 3rd graders of SD Negeri Pujokusuman academic year of 2017/2018. The selected sample was 3rd graders A, B, and C chosen by using cluster random sampling techniques. 3rd graders in class B as the control group, while 3rd graders in class A and C as group experiments. The control group was given preferential treatment by using the method of storytelling, while the experimental groups were given a treatment using the LVEP. Data collection techniques used is observation and interview. The guidelines for observation is conducted to know whether the students show/perform character nationalism before treatment (pretest), during treatment, and after treatment (posttest). The interview guidelines are used to support the observation, which cover up character of students, learning model character, and implementation of learning before they are treated with certain experiment. The data analysis techniques used was t-test with the level of significance 0,05. The research results show that there are significant impacts during nationalistic character building by implementing Living Values Education Program (LVEP), which is done through storytelling method in thematic learning for 3rd graders of SD Negeri Pujokusuman. Distinction appears vividly in all sub nationalistic character, which is observed during the learning process, namely responsibility, tolerance, cooperation, unity, love, respect, and peace.